Developing a K-12 Rural School System Wellness Policy through Community Engagement - Joseph A. Brosky, Jr; Mark R. Wiegand; Alana Bartlett; Tiffany Idlewine (The University of Alabama, 2022)
The Education Strategic Plan of the American Physical Therapy Association (APTA) outlines initiatives for professional practice, including enhancing physical therapists' roles in: 1) social, governmental, and regulatory practices and policies, 2) health promotion and wellness, and, 3) assessment of societal needs and health disparities. In this paper we describe a community partnership that involved development and implementation of a wellness policy for a rural public school system. A partnership was established to achieve compliance with government mandates for physical activity, nutrition standards, and school-based activities. Collaborative meetings with stakeholders identified the following issues: limited school expertise and resources, community awareness, resistance to change, and sensitivity of dealing with childhood obesity. A comprehensive wellness policy was developed and implemented. Opportunities were found to exist in local communities for health professionals and students to use their intellect, talents, and skills to meet educational objectives related to social responsibility, advocacy, disease prevention, and wellness. Service-learning experiences provided leadership opportunities to promote the role of physical therapists beyond traditional settings through community engagement.